The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41698-023-00378-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete response to alectinib in ALK-fusion metastatic salivary ductal carcinoma

Abstract: The advent of next-generation sequencing (NGS) has allowed for the identification of novel therapeutic targets for patients with uncommon cancers. It is well known that fusion translocations are potent driver of cancer pathogenesis and can render tumors exquisitely sensitive to matching targeted therapies. Here we describe a patient with ALK-fusion positive widely metastatic salivary ductal carcinoma, who achieved a durable complete response from alectinib, a potent and specific ALK tyrosine kinase inhibitor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…NRG1 fusion-bearing cancers may be therapeutically important. Fusions of several different gene types (e.g., BCR-ABL , NTRK , and RET fusions) are known drivers of cancer, and several successful therapies have been developed to target them [ 62 69 ]. Moreover, a recent study suggested that not targeting a fusion, if present, is associated with poorer clinical outcome even when genomic co-alterations are targeted [ 62 ].…”
Section: Main Textmentioning
confidence: 99%
“…NRG1 fusion-bearing cancers may be therapeutically important. Fusions of several different gene types (e.g., BCR-ABL , NTRK , and RET fusions) are known drivers of cancer, and several successful therapies have been developed to target them [ 62 69 ]. Moreover, a recent study suggested that not targeting a fusion, if present, is associated with poorer clinical outcome even when genomic co-alterations are targeted [ 62 ].…”
Section: Main Textmentioning
confidence: 99%
“…Although rare, ALK translocations represent an important therapeutic target in many solid tumors beyond NSCLC. For example, rare cancers such as papillary renal cell carcinoma and salivary ductal carcinoma have also shown sensitivity to alectinib [103,110].…”
Section: Alkmentioning
confidence: 99%
“…From a tumor biology perspective, the concern is a lack of actionable targets. NGS has been widely recognized in solid tumors as a way to identify clinically actionable genomic alterations [ 88 , 89 ], especially for tissue agnostic agents [ 90 , 91 ]. It has been reported previously that the rate of such alterations may vary from 40 to 94% [ 92 ].…”
Section: Mirvetuximab Soravtansine (Elahere™)mentioning
confidence: 99%